2008
DOI: 10.1007/s00213-008-1093-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of methylphenidate self-administration and reinstatement in the rat

Abstract: These results demonstrate that intravenous methylphenidate is a reinforcer and that its reinforcing efficacy is related to increased dopamine activity at D1 and D2 receptors. Methylphenidate reinstates drug-seeking behaviour; the route of administration modifies this response suggesting that pharmacokinetic factors are important in determining methylphenidate-induced reinstatement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 83 publications
6
49
1
1
Order By: Relevance
“…Methylphenidate self-administration on a PR schedule After completion of methylphenidate self-administration tests under the FR schedule, rats were trained to respond for methylphenidate under the progressive ratio (PR) schedule. The methods employed were the same as those outlined by Botly et al (2008), with some modifications. The methylphenidate dose used to train the rats in this schedule was 0.125 mg per infusion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methylphenidate self-administration on a PR schedule After completion of methylphenidate self-administration tests under the FR schedule, rats were trained to respond for methylphenidate under the progressive ratio (PR) schedule. The methods employed were the same as those outlined by Botly et al (2008), with some modifications. The methylphenidate dose used to train the rats in this schedule was 0.125 mg per infusion.…”
Section: Methodsmentioning
confidence: 99%
“…Over this period, rats acquired active self-administration based on significantly higher rate of lever response for the active than the inactive lever (95% confidence limit). During these sessions, both levers (active and inactive [non-reinforced]) were present, and a response on the active lever resulted to the delivery of 0.1 ml methylphenidate (0.25 mg) (Botly et al 2008) and the illumination of the stimulus light above it. The light was lit for 10 s and remained illuminated for 20 s after the end of the infusion.…”
Section: Methodsmentioning
confidence: 99%
“…The dose for the SCH-23390 was chosen based on previous work by Meririnne et al [12], which showed that these doses were sufficient to alleviate MPH-induced CPP in adult male rats. The doses for eticlopride HCl were based on past work by Botly et al [33], which demonstrated that these doses were sufficient to increase the number of infusions taken by rats trained to self-administer MPH. A two-way ANOVA was used as the primary statistic and Dunnett's multiple comparison test (p = 0.05) was used for all post hoc analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Notwithstanding this trend, there is concern that the rise in therapeutic use of MPH might coincide with a rise in its nontherapeutic, nonmedical (mis)use. Intranasal MPH produces a euphoric sensation or "high" in humans (Volkow and Swanson 2003), and rats readily self-administer this drug intravenously (Collins et al 1984;Fletcher et al 2007;Botly et al 2008). College students and adolescents might be attracted to MPH for its attention-focusing, weight-loss, or euphoric effects.…”
Section: Adhd and The Use Of Mphmentioning
confidence: 98%